Green synthesis and characterization of NiO/Hydroxyapatite nanocomposites in the presence of peppermint extract and investigation of their antibacterial activities against Pseudomonas aeruginosa and Staphylococcus aureus - Ali Shakerimoghaddam; Hayder Jihad Majeed; Ali Jawad Hashim; May Jaleel Abed; Layth S. Jasim; Masoud Salavati-Niasari (Results in Chemistry)
In many areas, antibiotic resistance is becoming a serious concern for public health. As a result of the interesting structural properties of nanomaterials, nanoscience-based methods have emerged as promising ways to increase the movement of existing antimicrobials. In this study, pristine nickel oxide (NiO) nanoparticles, hydroxyapatite (HAP) nanoparticles, and binary nickel oxide/hydroxyapatite (NiO/HAP) nanocomposites were fabricated through peppermint extract-assisted green route. The obtained results revealed that peppermint extract can be a superior green capping agent for the preparation of NiO, HAP, and NiO/HAP nanomaterials. The bioactivity tests revealed the bactericidal and anti-biofilm activities of synthesized NiO, HAP, and NiO/HAP nanostructures against Pseudomonas aeruginosa (PAO1) and Staphylococcus aureus (ATCC 43300) bacteria. The findings confirmed that the prepared NiO/HAP nanocomposites have more effective antibacterial activity than pure NiO and HAP. For Staphylococcus aureus, the minimal inhibitory concentration (MIC) values for NiO, HAP, and NiO/HAP nanocomposites were determined to be of about 9.60, 13.03, and 3.41 mg/mL, respectively. For Pseudomonas aeruginosa, the MIC values for NiO, HAP, and NiO/HAP nanocomposites were estimated as 9.6, 13.50, and 1.7 mg/mL, respectively. Although, all synthesized samples are remarkable in their ability to prevent the formation of biofilms at MIC and sub-MIC concentrations (p < 0.01), NiO/HAP illustrated biofilm inhibitory activity up to 95 % for Pseudomonas aeruginosa and to 81 % for Staphylococcus aureus. In the present study, it was demonstrated that NiO/HAP nanocomposites prepared in a green environment can be excellent antibacterial agents against Staphylococcus aureus and Pseudomonas aeruginosa.